Analisis Faktor-Faktor Yang Mempengaruhi Opini Auditgoing Concern Pada Perusahaan - Amanda Aprilia Firdaus; Tumirin Tumirin (Journal of Culture Accounting and Auditing, 2022)
This study aims to analyze the effect of debt default, opinion shopping, previous year's audit opinion, and disclosure on going concern audit opinion taken by the auditor. The population in this study were banking companies listed on the Indonesia Stock Exchange in 2013-2016. The research sample was taken using purposive sampling as many as 124 banking companies. This study uses logistic regression analysis. The results of this study can be concluded that debt default has a positive and significant effect on the acceptance of going-concern audit opinion. Opinion shopping has no effect on the acceptance of going-concern audit opinion. The previous year's audit opinion had a positive and significant impact on the going concern audit opinion acceptance. Disclosure has no effect on the acceptance of going concern audit opinion.